Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian : Survei pada Konsumen Batavia Fried Chicken Kawalu Kota Tasikmalaya - Annisa Fitriani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the simultaneous and partial effect of product quality and brand image on consumer purchasing decisions for fried chicken Batavia Kawalu, Tasikmalaya City. The research method used in this research is a quantitative approach with a survey method. population in this study amounted to 100 respondents. The type of data used in this study is primary data obtained through a data questionnaire. Analysis of the data used is multiple linear regression analysis, correlation and coefficient of determination. The results of this study indicate that product quality and brand image simultaneously have a significant effect on purchasing decisions on fried chicken Batavia Kawalu, Tasikmalaya City. Product quality partially had a significant effect on purchasing decisions for fried chicken Batavia Kawalu in Tasikmalaya City.